Inoculation With Azospirillum spp. Acts as the Liming Source for Improving Growth and Nitrogen Use Efficiency of Potato - Naqqash, Tahir; Malik, Kauser Abdullah; Imran, Asma; Hameed, Sohail; Shahid, Muhammad; Hanif, Muhammad Kashif; Majeed, Afshan; Iqbal, Muhammad Javed; Qaisrani, Muther Mansoor; van Elsas, Jan Dirk (Frontiers in Plant Science, 2022)
Nitrogen (N) is one of the limiting factors for plant growth, and it is mainly supplied exogenously by fertilizer application. It is well documented that diazotrophic rhizobacteria improve plant growth and development by fixing atmospheric N in the soil. The present study investigates the nitrogen-fixing potential of two Azospirillum spp. strains using the 15N isotope-dilution method. The two diazotrophic strains (TN03 and TN09) native to the rhizosphere of the potato plant belong to the Azospirillum genus (16S rRNA gene accession number: LN833443 and LN833448, respectively). Both strains were able to grow on an N-free medium with N-fixation potential (138-143 nmol mg-1 protein h-1) and contained the nifH gene. Of two isolates, TN03 showed higher IAA production (30.43 μg/mL), while TN09 showed higher phosphate solubilization (249.38 μg/mL) while both diazotrophs showed the production of organic acids. 15N dilution experiment was conducted with different fertilizer inputs to evaluate the N-fixing potential of both diazotrophs in pots. Results showed that plant growth parameters and N content improved significantly by PGPR inoculation while produced reduced 15N enrichment compared to uninoculated controls that also received a similar concentration of N fertilizer. The decreased 15N enrichment validates the occurrence of N-fixation through isotopic dilution. TN09 showed higher N-fixing potential compared to TN03 and uninoculated controls. Inoculation with Azospirillum spp. (TN03 and TN09) also showed a remarkable increase in plant growth parameters in field conditions. There was a remarkable increase in N use efficiency, N uptake and N utilization of potato plants under field conditions. The analysis of root colonization using confocal laser scanning, and transmission electron microscopy showed that TN03 is an ectophyte i.e., present outside the root cells or within the grooves of root hairs, while TN09 was found to be an endophyte i.e., present within the root cell forming a strong association with the root cell. This study validates that the inoculation of diazotrophic Azospirillum spp. improved potato growth and N use efficiency, suggesting that there could be an opportunity to improve plant growth with reduced input of N fertilizer by combining with rhizobacterial strains that promote yield and growth.